PENGARUH KUALITAS AUDIT, KARAKTERISTIK CORPORATE GOVERNANCE, KEPEMILIKAN PUBLIK, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP AUDIT REPORT LAG (Studi Empiris pada Perusahaan Non-Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2017) - Annisa Dwi Arizky; Agus Purwanto (Diponegoro Journal of Accounting, 2018)
The purpose of this research is to examine the effect of audit quality, characteristic of corporate governance, public ownership, company size, and profitability on audit report lag. Dependent variable used in this research is audit report lag. Independent variables used in this research are auditor specialist, auditor reputation, independent commissioner, audit committee, public ownership, company size, and profitability. Data used in this research is secondary data which collected using purposive sampling method. Sample of this research consists of 801 public companies that listed in Indonesian Stock Exchange (IDX) during 2016-2017. Analysis technique used in this research is multiple regression. The result of this research shows that auditor specialist, independent commissioner, company size, and profitability has negative effect on audit report lag. While auditor reputation, audit committee, and public ownership doesn’t have effect on audit report lag.